Fatty Aldehyde and Fatty Alcohol Metabolism: Review and Importance for Epidermal Structure and Function - Rizzo, William B. (2013)
Normal fatty aldehyde and alcohol metabolism is essential for epidermal differentiation and function. Long-chain aldehydes are produced by catabolism of several lipids including fatty alcohols, sphingolipids, ether glycerolipids, isoprenoid alcohols and certain aliphatic lipids that undergo α- or ω-oxidation. The fatty aldehyde generated by these pathways is chiefly metabolized to fatty acid by fatty aldehyde dehydrogenase (FALDH, alternately known as ALDH3A2), which also functions to oxidize fatty alcohols as a component of the fatty alcohol:NAD oxidoreductase (FAO) enzyme complex. Genetic deficiency of FALDH/FAO in patients with Sjögren-Larsson syndrome (SLS) results in accumulation of fatty aldehydes, fatty alcohols and related lipids (ether glycerolipids, wax esters) in cultured keratinocytes. These biochemical changes are associated with abnormalities in formation of lamellar bodies in the stratum granulosum and impaired delivery of their precursor membranes to the stratum corneum (SC). The defective extracellular SC membranes are responsible for a leaky epidermal water barrier and ichthyosis. Although lamellar bodies appear to be the pathogenic target for abnormal fatty aldehyde/alcohol metabolism in SLS, the precise biochemical mechanisms are yet to be elucidated. Nevertheless, studies in SLS highlight the critical importance of FALDH and normal fatty aldehyde/alcohol metabolism for epidermal function.